2018
DOI: 10.1055/s-0037-1612633
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Finding of Ectopic Adrenocortical Tissue in a 2-Year-Old Boy with Vanishing Testis

Abstract: Ectopic adrenocortical tissue (EAT) along the spermatic cord is an unusual condition in children. The author reports on a 2-year-old boy with impalpable testis. On laparoscopy, EAT was detected along the hypotrophic spermatic vessels and excised. These remnants should be removed to prevent hormone production or malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The ideal follow-up interval after conservative treatment of benign testicular tumors is still not well defined. Patients with Leydig cell tumors, as well as complex epidermoid cysts, should be followed by medical monitoring, including a clinical examination and US, although the frequency of these medical evaluations and the duration are still debated Wegner et al [13] found one local recurrence after conservative therapy and no progressive disease after reviewing 15 patients with Leydig cell tumors [14][15][16][17]. Interestingly, our Series includes 3 cases of LCCSCT.…”
Section: Discussionmentioning
confidence: 92%
“…The ideal follow-up interval after conservative treatment of benign testicular tumors is still not well defined. Patients with Leydig cell tumors, as well as complex epidermoid cysts, should be followed by medical monitoring, including a clinical examination and US, although the frequency of these medical evaluations and the duration are still debated Wegner et al [13] found one local recurrence after conservative therapy and no progressive disease after reviewing 15 patients with Leydig cell tumors [14][15][16][17]. Interestingly, our Series includes 3 cases of LCCSCT.…”
Section: Discussionmentioning
confidence: 92%